Bio-waste as an Alternative Source of Fossil Fuel in Iraq - Atheel Alwash; Mohammed Kadhom; Emad Yousif; Omar Al-Obaidi; Muna Bufaroosha (مجلة جامعة الانبار للعلوم الصرفة)
With considerable potential advantages, including decreased reliance on fossil fuels, waste management, economic prospects, and environmental benefits, the idea of using bio-waste as an alternative to fossil fuels in Iraq is an attractive one. Additionally, the government must contend with issues related to feedstock availability, policy and regulation, societal acceptability, and technological infrastructure. The potential of bio-waste is a promising target; yet, overcoming the challenges requires a multi-pronged approach. Collaboration between the government, private sector, research institutions, and local communities is the key to developing a sustainable and economically viable bio-waste-to-fuel industry in Iraq.